AUTHORITY TO RESOLVE DISPUTES OF STATE ADMINISTRATION S AGAINST THE RESIGNATION DECISION WITHOUT RESPECT - Imawan Sugiharto; Andi Zulfa Majida (Adisam Publisher, 2024)
The dismissal of disrespectful public officials becomes a complex focus in state administration law, posing a major challenge in the settlement of disputes by the State Administration Court. (PTUN). Such cases involve complex and diverse legal considerations, requiring a careful and detailed approach from law enforcement. Therefore, an in-depth understanding of the authority and procedures of the PTUN in controversial dismissal cases is essential to ensure fairness and compliance with applicable law. The purpose of writing this article is to know the authority of the PTUN in the settlement of the dispute of the state Administration against the decision of discontinuation not with respect and efforts to resolve it as a State Administration dispute The method of research used is normative jurisprudence. The settlement of civil disputes is resolved through the State Administration Court, unless the civil dispute resulting from the violation of the disciplinary rules of the State Civil Appliance is settled through an administrative appeal to the Court of Justice.